2023
DOI: 10.1039/d3ta02133e
|View full text |Cite
|
Sign up to set email alerts
|

Glucose oxidation assisted hydrogen and gluconic/glucaric acid production using NiVP/Pi bifunctional electrocatalyst

Abstract: Hydrogen is an efficient green energy source due to its high energy density and environmental friendliness. Water electrolyzer which involve hydrogen generation at the cathode and O2 production at the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…The comparative LSV curves demonstrate the superior performance of the Ru-Tta-Dfp catalyst among all of the variants witnessed by its lower overpotentials at 10 mA cm –2 (Table S8). Furthermore, the sequential chronoamperometric investigations were conducted using Ru-Tta-Dfp to ascertain the mass transport characteristics leading to glucose oxidation (Figure b) . As observed from Figure b, the current was almost negligible when the potential was swept from 1.0 V, and as the potential reached 1.2 V vs RHE, a rapid increase in the current density was observed, marking 1.2 V as the onset potential for GOR.…”
Section: Electrocatalytic Performance For Glucose Oxidation Reaction ...mentioning
confidence: 98%
See 1 more Smart Citation
“…The comparative LSV curves demonstrate the superior performance of the Ru-Tta-Dfp catalyst among all of the variants witnessed by its lower overpotentials at 10 mA cm –2 (Table S8). Furthermore, the sequential chronoamperometric investigations were conducted using Ru-Tta-Dfp to ascertain the mass transport characteristics leading to glucose oxidation (Figure b) . As observed from Figure b, the current was almost negligible when the potential was swept from 1.0 V, and as the potential reached 1.2 V vs RHE, a rapid increase in the current density was observed, marking 1.2 V as the onset potential for GOR.…”
Section: Electrocatalytic Performance For Glucose Oxidation Reaction ...mentioning
confidence: 98%
“…To take the NO 3 RR a step further, it is essential to consider the accompanying oxygen evolution reaction (OER) at the anode in the full cell (NO 3 RR-OER) electrolysis. The sluggish kinetics of OER due to high energy demand for O–O bond formation (4e – transfer) become the bottleneck for the effective synthesis of NH 3 . Alternatively, substituting the OER at the anode by other thermodynamically more feasible oxidation reactions, viz., the glucose oxidation reaction (GOR), thus decreases an energy input for ammonia synthesis along with the value-added products at the anode (NO 3 RR-GOR). This strategy provides a proficient assimilation of two industrially important areas, i.e., anodic oxidation of glucose to glucaric/gluconic acid along with enhanced ammonia production at the cathode while lowering the overall potential, subsequently increasing its economic value.…”
mentioning
confidence: 99%
“…A nickel vanadium phosphide/ phosphate-Vulcan carbon (NiVP/Pi-VC) catalyst was prepared, which reached 10 mA cm À 2 at 1.30 V vs. RHE and only slightly attenuated after 100 hours of electrolysis. [79] In addition, other researchers have also reported on Ni-MoS 2 NPs [80] and Co/CoP [81] catalysts.…”
Section: Glucosementioning
confidence: 99%
“…37 Recently, Thakur et al has showed the role of nickel vanadium phosphide/phosphate–Vulcan carbon (NiVP/Pi–VC) for glucose oxidation assisted H 2 production. 38…”
Section: Introductionmentioning
confidence: 99%
“…37 Recently, Thakur et al has showed the role of nickel vanadium phosphide/phosphate-Vulcan carbon (NiVP/Pi-VC) for glucose oxidation assisted H 2 production. 38 Nickel is an earth abundant, non-toxic, inexpensive, and possesses intrinsic redox behaviour (Ni 2+ /Ni 3+ ). For glucose oxidation, electron transfer is known to be mediated by Ni(OH) 2 /NiO(OH) redox couple, and participates in the rate limiting step of the electro-oxidation.…”
Section: Introductionmentioning
confidence: 99%